An Unusual Cause of Posterior Elbow Impingement: Detachment of a Hypertrophied Posterior Fat Pad. (3rd November 2015) - Hamada, Daisuke; Matsuura, Tetsuya; Sugiura, Kosuke; Higuchi, Tadahiro; Suzue, Naoto; Goto, Tomohiro; Tsutsui, Takahiko; Wada, Keizo; Fukuta, Shoji; Sairyo, Koichi
Abstract : We report a case of a 47-year-old woman who developed posterior impingement of the elbow due to detachment of a hypertrophied posterior fat pad. She reported acute left elbow pain after leaning back onto a hard object with her hand and subsequently experienced a "catching" sensation. Comparison with the magnetic resonance images of a normal elbow revealed a hypertrophied posterior fat pad interposed between the olecranon and olecranon fossa in both elbows, with the fat pad in the left elbow located more inferiorly than that in the right elbow. Elbow arthroscopy showed the olecranon fossa covered by the fat pad, a portion of which was detached from the rest of the pad. Debridement of the detached portion was performed until no impingement was evident. Postoperatively, full extension of the elbow did not elicit pain. Clinicians should include this pathology among the differential diagnoses for posterior elbow pain.